Trends and outcomes of thrombolytics in patients with STEMI - Pandey, Mandvi; Sivakumar, Nithila; Pujar, Sanjay; Pitta, Sridevi Reddy (International Journal of Research in Medical Sciences, 2024)
Background: In ST-segment elevation myocardial infarction (STEMI) percutaneous coronary intervention (PCI) is the gold standard, but the time/resource constraints can necessitate alternative approaches. This study aimed to analyze outcomes and predictors of in-hospital mortality in STEMI patients undergoing thrombolysis. Methods: A retrospective analysis of national inpatient sample data (2016-2020) included adult patients admitted with STEMI. Using ICD-10 procedural codes, patients undergoing thrombolysis or PCI were identified. Elixhauser’s comorbidity index identified comorbidities, and univariate and multivariate analyses adjusted for confounders. The primary outcome was mortality rates in STEMI patients undergoing thrombolysis versus PCI. Secondary outcomes were factors influencing mortality rates and major complications associated with thrombolysis. Results: Out of 819,979 patients diagnosed with STEMI, 0.2% (2349 patient’s) received thrombolysis as their primary treatment upon admission. The mortality rate among patients undergoing thrombolysis was 12.34% versus 4.09% with PCI. Additionally, a higher proportion of patients undergoing thrombolysis required left ventricular assist device (LVAD) (4.8% versus 0.89% in the PCI group), and the incidence of cardiogenic shock was significantly elevated in this cohort (10.8% versus 6.68% in the PCI group). Factors influencing in-hospital mortality among patients undergoing thrombolysis included age (with a 3% increase in mortality observed with each year of age), LVAD placement (patients with LVADs had 3.6 times higher odds of mortality compared to those without, with aOR 3.69, p=0.029, 95% CI 1.14-11.89), and the use of mechanical ventilation, which independently predicted mortality outcomes. Conclusions: Thrombolysis in STEMI patients is a vital alternative to PCI. It is associated with higher mortality and complications compared to PCI. Age, LVAD placement, and mechanical ventilation independently predict mortality. Identifying these factors can help us improve the outcomes of thrombolysis. Further prospective research is warranted to optimize outcomes in thrombolysis for STEMI.